Development of Criteria for the Effectiveness of Implementation of Value- Based Approach Using the Concept of Quality of Life - E. V. Smirnova (Здоровье мегаполиса, 2025)
Background. The results of the implementation of value-based healthcare principles are evaluated directly based on a set of indicators that aim to measure this effectiveness. However, the objectivity of such evaluations is often compromised due to the necessity of employing assessment scales that may reflect inconsistent perspectives among various stakeholders who organize and provide medical care. In order to optimally balance subjective and objective characteristics of effectiveness, it is crucial to incorporate the indicators of patient's quality of life and health—as one of the most important components—and the indicators of volume of financial costs to achieve good health, that fully reflect the outcomes of value-based healthcare measures.Purpose. The study offers a possible list of criteria for evaluating the effectiveness of implementation of value-based healthcare as well as a justification for criteria selection.Methods and materials. A content-analysis of key regulations governing the organization and provision of primary medical care to the adult population was carried out. Electronic science databases were used to search for scientific literature.